Exploring the Art School Pre-Application Portfolio Review - Macdonald, Meghan (The Canadian Art Teacher / Enseigner les arts au Canada, 2025)
In this article I hypothesize that the role of the pre-application portfolio review goes beyond an assessment of an individual’s readiness for a postsecondary program, but also offers important insight for the prospective applicant into program culture and student experience, providing helpful information to guide them toward a postsecondary offering.My central research question, which has evolved from my lens as a recruiter for NSCAD University and Nova Scotia Community College to arts education researcher, is:How could a pre-application portfolio review affect the art maker when submitting post-secondary portfolio applications and choosing a postsecondary path?On top of the academic requirements typical of postsecondary institutions, each institution and, in some cases, each program within an institution has written its own requirements for the portfolio portion of its application. As these requirements are conceived internally, they may present a window into the values and preferences of their faculty, and by extension the institution, as well as the limits of studio facilities. Engaging in a portfolio review is a way for prospective students to get feedback prior to finalizing and submitting their portfolio for application. At its best, the review is a critical support for learners and an institutional tool for recruitment and retention. What it also does, but may not always acknowledge, is offer students, for the first time in their careers, an opportunity for a one-to-one presentation of their work and lives, which can be fraught with uncertainty and a desire for direction and acknowledgement that their work and hopes are valid and worthy.